Achieving high current density for electrocatalytic reduction of CO2 to formate on bismuth-based catalysts - Fan, Tingting; Ma, Wenchao; Xie, Mingcan; Liu, Huan; Zhang, Jiguang; Yang, Shuangli; Huang, Pingping; Dong, Yunyun; Chen, Zhou; Yi, Xiaodong (Cell reports physical science, 2021)
Electrocatalytic reduction of CO2 to formate is an attractive avenue for CO2 utilization. Unfortunately, existing catalysts suffer from low faradic efficiency of formate production at high current density. Here, we report a general strategy for preparing the Bi2O2CO3 nanosheet (BOC-NS) with abundant oxygen vacancies through in situ electrically driven conversion of the BiPO4 precursor. The converted BOC-NS displays high faradic efficiency of formate (FEHCOO−) (∼100%) over a wide potential region in an H-type cell and achieves a formate partial current density of −930 mA cm−2 with a FEHCOO− of 93% at −1.55 VRHE in a flow cell. Experimental results and density functional theory (DFT) calculations confirm that the BOC-NS surface with abundant oxygen vacancies benefit formate production, which stems from fast reaction kinetics toward the formation of ∗OCHO intermediate on defective Bi2O2CO3 nanosheets. This work provides helpful guidance for designing efficient electrocatalysts via in situ electrochemical transformation. [Display omitted] Defective Bi2O2CO3 nanosheet is prepared through in situ conversion of BiPO4Bi2O2CO3 serves as a stable and active phase for CO2RR to formateBOC-NS displays superior CO2RR performance toward formateDFT study confirms that oxygen vacancy benefits formate production Fan et al. present the production of defective Bi2O2CO3 nanosheet through in situ transformation of BiPO4, which achieves a high formate partial current density of −930 mA cm−2 with a faradic efficiency of 93% in a flow cell. This material contains beneficial oxygen vacancies and shows improvement over existing catalysts that suffer from low faradic efficiency of formate production at high current density.